Packaging of humanized anti-HER2 monoclonal antibody into small extracellular vesicles - Junxin Mai; Yuanmei Zhang; Zhixuan Liang; Wei Xu; Qian Shao; Jingwen Peng; Jing Chen; Yuting Shentu; Zixin Chen; Juling Ji; Yuhua Ji; Qiuling Xie (Extracellular Vesicle)
Small extracellular vesicles (sEVs), including exosomes and microvesicles (MVs), are nano-sized membranous particles shed by almost all cell types. Both play significant roles in cellular communication by transferring proteins, nucleic acids, lipids, and metabolites to recipient cells and impact a broad range of pathophysiological processes, whereby they hold great promise in clinical application as therapeutic cargo carriers. Previous studies have shown that the membrane antibodies on exosomes derived from primary B cells, B cell lines, and hybridoma can present antigen-induced T cell responses. However, whether secretory antibodies can be released by sEVs and play a biological role has been unclear. Antibody against human epidermal growth factor receptor-2 (HER2 antibody) is a humanized monoclonal IgG antibody. In this study, by using a CHO cell line expressing recombinant anti-HER2 monoclonal antibody (CHO-HER2), we demonstrated the packaging of the intact HER2 antibodies in the sEVs (sEVs-HER2), and the involvement of endocytosis in their anti-proliferation effects on the BT474 cells, a HER2-overexpressing cell line. Further unbiased proteomic analysis showed that the heavy and light chains of IgG were the most abundant sEVs proteins and revealed that besides endosomal and lysosomes proteins, the proteins involved in the Golgi apparatus were significantly enriched in sEVs-HER2. Brefeldin A (BFA), a potent inhibitor of protein trafficking from the endoplasmic reticulum (ER) to the Golgi apparatus, significantly suppressed the titer of anti-HER2 antibody in both supernatant and sEVs-HER2. Moreover, the HER2 antibodies in the sEVs could be significantly suppressed by Tipifarnib and Y27632, inhibitors targeting exosomes and MV biogenesis/release, respectively. This study demonstrated that the secretory HER2 antibody could be packaged into sEVs and maintain its anti-proliferation activity. Moreover, this study suggested that the HER2 antibodies could be packaged in both exosomes and MVs and the involvement of the Golgi pathway.